'Discursive struggles' between criminal justice sanctions and health interventions for people who use drugs: a qualitative exploration of diversion policy and practice in Scotland. (4th March 2021) - Price, T.; Parkes, T.; Malloch, M.
Abstract: Amidst growing recognition that people who use drugs are often vulnerable and in need of health-focused support, international conventions and national priorities on personal drug use are changing with emphasis shifting from criminal justice to health narratives. In Scotland, there has been a move toward health-led drug policymaking, and yet little is known about how diversion operates in this context. An exploratory qualitative study was conducted utilizing semi-structured interviews with professionals holding lead, strategic-level roles in Scottish diversion policy and practice ( n = 15). Interview transcripts were thematically analyzed using a structured framework technique. Findings show that the term 'diversion' is used to refer to criminal justice-initiated drug treatment routes, both pre- and post-conviction. Unlike many international examples, Scottish diversions tend to embed health-focused support within criminal sanctions, rather than acting as alternatives. Participants expressed the view that the term diversion implied a shift from criminal justice sanctions to health-led support that did not occur in reality. We, therefore, argue that the term diversion may function to mute a 'discursive struggle' between criminal justice sanctions and health interventions for people who use drugs, obscuring a growing gap between aspirational governance principles and institutional and lived realities.